CRIMINAL TERRORIST GROUP IN THE NEW CRIMINAL LEGISLATION OF ROMANIA - Mirela GORUNESCU (Challenges of the Knowledge Society)
In the Romanian criminal law, there is a specialized regulation that defines criminal terrorist group, as variant of plurality of offenders. The present study presents this kind of criminal group by identifying the elements of differentiation compared to the organized crime group regulated by the Criminal Code).